The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s00268-013-2190-7
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Hepatectomy for Recurrent Liver Metastasis From Gastric Carcinoma

Abstract: In selected patients, repeat hepatectomy for recurrent gastric cancer liver metastasis may offer the same chance of cure as the primary hepatectomy. Disease-free intervals exceeding 12 months predict good patient survival after repeat hepatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Repeat hepatectomy was performed in only 14·4 per cent of patients. Compared with liver metastases from colorectal cancer, there is less opportunity for repeat hepatectomy for GCLMs because the recurrence pattern is more complex; however, repeat hepatectomy can be considered if the hepatic recurrence is solitary.…”
Section: Discussionmentioning
confidence: 99%
“…Repeat hepatectomy was performed in only 14·4 per cent of patients. Compared with liver metastases from colorectal cancer, there is less opportunity for repeat hepatectomy for GCLMs because the recurrence pattern is more complex; however, repeat hepatectomy can be considered if the hepatic recurrence is solitary.…”
Section: Discussionmentioning
confidence: 99%
“…Takemura et al [26] reported a 5-year survival rate and MST of 47 % and 31 months, respectively, in 14 patients who underwent repeat hepatectomy for recurrence in the liver remnant. Two of the three patients who underwent repeat hepatectomy in our study also achieved long-term survival, suggesting that resection may be considered if the aforementioned indications are met.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, overall 5-year survival rate of gastric cancer metastatic to the liver ranges between 0 and 10% [58,59,92], whereas it rises up to 20% after curative hepatectomy in the literature [64-68, 73, 93]. Furthermore, taking into consideration the only article about hepatic metastasis local re-treatment after recurrence, the authors found a survival advantage in local treatment repetition [94].…”
Section: Liver Metastases From Gastric Cancermentioning
confidence: 97%